Mainports as Integrators of Passenger, Freight and Information Networks. From Transport Nodes to Business Generators; the Dutch Case - Priemus, Hugo (European Journal of Transport and Infrastructure Research, 2001)
In the process of increasing globalization, mainports play an important role. A number of gateways have emerged as transport nodes in the networks of air and sea routes which crisscross the globe. Here, millions of travellers are transferred and millions of tonnes of freight are transhipped. Both Japan and the Netherlands play an important part in these ‘hub and spoke’ networks. In this contribution we will deal with the dynamics of mainports in general, and more specifically with the mainports of the Netherlands. Our argument is that their function goes far beyond that of infrastructure, transport and logistics. Although they started out as transport nodes, the mainports in the Netherlands are now evolving into fully fledged business generators. The economic function of mainports will be strengthened by integrating mainport and brainport functions. It will be further reinforced by seizing the opportunity to combine the traditional mainport functions. This will involve connecting airlines with road and rail transport networks, connecting ocean shipping with inland shipping, cargo trains, trucks and pipelines and connecting transport nodes with an infrastructural node of ICT (information and communications technology) networks. For the Randstad Holland (the Netherlands’ economic heartland in the west), we conclude that a stronger integration of gateway Rotterdam and mainport Amsterdam Schiphol could be considered. This could be achieved not only by strengthening their transport infrastructure, but first and foremost by planning, developing and integrating the ICT mainport functions.